UNCONVENTIONAL MONETARY POLICY OF THE EUROPEAN CENTRAL BANK (EU and comparative law issues and challenges series (ECLIC), 2019)
Central banks control and manage the amount of money in the economy by steering short-term interest rates. Conventional short-term interest rate monetary policy has its limitations and the limit is zero lower bound. Zero lower bound means that the short-term interest rate cannot be set below 0%. Managing the level of short-term interest rate a central bank can influence the overall availability and cost of credits and control the quantity of money in economy. If the level of the inflation rates are low and economic growth is weak a central bank can lower short-term interest rate to increase money supply in the economy. After the 2008 financial crisis, the European Central Bank reduced short-term interest rates to zero or near zero to stimulate spending and investing with the expectations that this measure would be enough to induce economic growth in the euro area. Contrary to expectations, lowering short-term interest rates had little effects on economy in the euro area. Economic growth stagnated, inflation rates were very low with a tendency to deflation and the rate of the employment was low. Similar effects occurred in other countries where central banks also lowered short-term interest rates to zero or near zero. Since then, the European Central Bank and other central banks did not achieve expected results using conventional short-term interest rates monetary policy so they had to use some other unconventional and non-standard monetary policy measures. The European Central Bank conducted Asset purchases programme (APP) and Longer-term refinancing operations (LTRO) as non-standard monetary policy measures and unconventional balance sheet monetary policy. In this paper, these non-standard measures of the European Central Bank monetary policy will be explained. Characteristics of each measure will be provided and the measures will be compered. The European Central Bank has adopted a decision for each of the measures and those decisions as a legal basis for each of the measure will be given and explained. The European Central Bank expected some results and those expected results will be compared with achieved results of these non-standard measures. Alternative measures and other policies that can improve effectiveness of the unconventional monetary policy measures will be suggested and explained.